2010
DOI: 10.3390/en3040784
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Harvesting Sun Light for Silicon Solar Cells through Advanced Optical Couplers and A Radial p-n Junction Structure

Abstract: Abstract:Silicon-based solar cells (SCs) promise to be an alternative energy source mainly due to: (1) a high efficiency-to-cost ratio, (2) the absence of environmentaldegradation issues, and (3) great reliability. Transition from wafer-based to thin-film SC significantly reduces the cost of SCs, including the cost from the material itself and the fabrication process. However, as the thickness of the absorption (or the active) layer decreases, the energy-conversion efficiency drops dramatically. As a consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Numerous methods have been used to increase the conversion efficiency of HCPV [1][2][3]. Despite its high efficiency in all types of solar cells, 60%-64% of collected solar energy is transformed into heat rather than electricity.…”
Section: Open Accessmentioning
confidence: 99%
“…Numerous methods have been used to increase the conversion efficiency of HCPV [1][2][3]. Despite its high efficiency in all types of solar cells, 60%-64% of collected solar energy is transformed into heat rather than electricity.…”
Section: Open Accessmentioning
confidence: 99%
“…Experimentally, Si nanowire solar cells (NW SCs) showed an enhancement in external quantum efficiency and absorption efficiency . Silicon radial p–n and p–i–n junction arrays achieved solar energy conversion efficiency of 10% under AM1.5G illumination when fabricated by low‐temperature epitaxial growth process using silane‐based chemical vapor deposition .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some researchers have shown that the scattering of solar radiation from nanoparticles, if suitably located and sized, may considerably improve the functioning of the thin-film cells [6][7][8]. The light is scattered and trapped into the silicon substrate by multiple and high-angle scattering, causing an increase of the effective optical path length in the cell and, consequently, enabling the improvement of its efficiency.…”
Section: Introductionmentioning
confidence: 99%